Volume 5B: Heat Transfer 2016
DOI: 10.1115/gt2016-57318
|View full text |Cite
|
Sign up to set email alerts
|

Design for Additive Manufacturing: Internal Channel Optimization

Abstract: The new possibilities offered by Additive Manufacturing (AM) can be exploited in gas turbines to produce a new generation of complex and efficient internal coolant systems. The flexibility offered by this new manufacturing method needs a paradigm shift in the design approach and a possible solution is offered by Topology Optimization. The overall goal of this work is to propose an innovative method to design internal channels in gas turbines that that fully exploit AM capabilities. The present w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Dede et al [32] used topology optimization to additively manufacture a heat sink for electronics cooling; the authors' optimized heat sink showed higher heat transfer performance than their baseline. Other topology optimization studies [33,34] have been numerical in nature, but show great promise for future production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dede et al [32] used topology optimization to additively manufacture a heat sink for electronics cooling; the authors' optimized heat sink showed higher heat transfer performance than their baseline. Other topology optimization studies [33,34] have been numerical in nature, but show great promise for future production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A high-performance chassis design of an automotive vehicle body has been innovated using topological optimization [3]. Similar approaches have been used to improve the design procedure for turbomachinery components, especially if combined with additive manufacturing techniques [4][5][6][7][8]. Referring to railway applications, the anchor bracket has been redesigned by taking advantage of a topology optimization process and introducing composite materials [9].…”
Section: Introductionmentioning
confidence: 99%
“…Favourable cells are then rewarded by increased permeability and counterproductive cells penalised by reducing their permeability. Over several iterations, the optimised fluid path is revealed as the regions in which sensitivities remained favourable and the permeability stayed high enough for the region to be considered fluid (Pietropaoli et al 2016). The corresponding optimised solid geometry is taken as the opposing regions in Responsible Editor: Emilio Carlos Nelli Silva which the permeability has been reduced to zero.…”
Section: Introductionmentioning
confidence: 99%